2015
DOI: 10.1096/fj.15-272955
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein signaling promotes morphogenesis of blood vessels, wound epidermis, and actinotrichia during fin regeneration in zebrafish

Abstract: Zebrafish fin regeneration involves initial formation of the wound epidermis and the blastema, followed by tissue morphogenesis. The mechanisms coordinating differentiation of distinct tissues of the regenerate are poorly understood. Here, we applied pharmacologic and transgenic approaches to address the role of bone morphogenetic protein (BMP) signaling during fin restoration. To map the BMP transcriptional activity, we analyzed the expression of the evolutionarily conserved direct phospho-Smad1 target gene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 47 publications
(88 reference statements)
2
31
0
Order By: Relevance
“…The fin skeleton includes a fish-specific structure, the actinotrichia, which rely on evolutionarily conserved mechanisms to regulate their regeneration. Désirée König (Jazwinska laboratory, Fribourg University, Switzerland) showed that a complex mixture of growth factors (TGFβ, FGF, BMP) is required to regrow actinotrichia (Thorimbert et al, 2015).…”
Section: Blastema Dynamics and Tissue Remodelingmentioning
confidence: 99%
“…The fin skeleton includes a fish-specific structure, the actinotrichia, which rely on evolutionarily conserved mechanisms to regulate their regeneration. Désirée König (Jazwinska laboratory, Fribourg University, Switzerland) showed that a complex mixture of growth factors (TGFβ, FGF, BMP) is required to regrow actinotrichia (Thorimbert et al, 2015).…”
Section: Blastema Dynamics and Tissue Remodelingmentioning
confidence: 99%
“…; Thorimbert et al. ) is different to that shown by ray blastema (Yoshinari et al. ; Marí‐Beffa & Murciano, ; Whener et al.…”
Section: Discussionmentioning
confidence: 81%
“…), id1 (Thorimbert et al. ) in zebrafish or the tms β‐like gene in Xiphophorus (Offen et al. ) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in the formation of an apical epidermal cap, which signals for the dedifferentiation of cells to form the distal blastema. Amputated zebrafish embryos obtained from a ptena +/− ptenb −/− in‐cross were fixed at 3 h post amputation (hpa) and subjected to in situ hybridization for detection of mmp9 transcription, which is a marker for the wound epithelium (Yoshinari, Ishida, Kudo, & Kawakami, 2009), and junbb and and1 transcription, both of which have previously been shown to be upregulated in the blastema (Thorimbert et al., 2015; Yoshinari et al., 2009). In fact, junbb expression is maintained well into the initial stage of regenerative outgrowth, indicating that junbb is a definitive distal blastema marker (Ishida, Nakajima, Kudo, & Kawakami, 2010).…”
Section: Blastema Formation Marker Suggests That the Initial Responsementioning
confidence: 99%